KAT2B inhibits proliferation and invasion via inactivating TGF-β/Smad3 pathway-medicated autophagy and EMT in epithelial ovarian cancer - Yuqin Yao; Yuna Niu; Honggui Zhou; Min Yong (Scientific Reports)
Abstract Lysine acetyltransferase 2B (KAT2B) plays a crucial role in epigenetic regulation and tumor pathogenesis. Our study investigates KAT2B’s function in epithelial ovarian cancer (EOC) using in vivo and in vitro methods. Immunohistochemistry showed the KAT2B expression in EOC tissues. RNA sequencing (RNA-seq) further identified altered gene expression profiles following KAT2B silencing in EOC cells. Western blot and qRT-PCR were employed to assess the protein and mRNA expression, respectively. KAT2B downregulated in EOC tissues and correlated with both FIGO stage and grade. KAT2B silencing induced autophagy, enhancing cell proliferation and invasion, while overexpression had opposite effects. In vivo, KAT2B silencing increased tumor volume and weight, mitigated by autophagy inhibitor chloroquine. Bioinformatics and co-immunoprecipitation assays identified a KAT2B-SMAD7 interaction. Mechanistic investigations suggested that KAT2B knockdown enhanced autophagy via activation of the TGF-β/Smad3/7 signaling pathway, thereby driving epithelial-mesenchymal transition (EMT), proliferation, and invasion in EOC. Additionally, our data hint at a potential role for the AKT/mTOR pathway. KAT2B acts as a putative tumor suppressor in EOC, where its reduced expression correlates with advanced disease stages. It is implicated in the regulation of autophagy, proliferation, and invasion via the TGF-β/Smad3/7 pathway, positioning KAT2B as a candidate therapeutic target for EOC interventions.